Assessment of variations in arterial tone during different phases of menstrual cycle - Umapathy, E.; Muthiraparampil, S. T.; Namugowa, A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Arterial tone parameters in young African women during the different phases of menstrual cycle were assessed in the present study. Methods: Out of the 30 student volunteers who participated in the study, only 15 completed the study. Anthropometric data using stadiometer, blood pressure using automated oscillometric pressure gauge were measured. Arterial stiffness parameters at the radial and ECG gated carotid and femoral arteries using sphygmocor tonometry was mesured in two consecutive menstrual cycles at early follicular, ovulation and luteal phase. Estrogen and progesterone concentrations were analyzed using Elisa kits in all three phases. Results: Estrogen level in ovulation phase and progesterone in luteal phase were higher. Peripheral augmentation index in ovulation phase was higher compared to luteal phase. Pulse pressure amplification value at follicular and luteal phases was higher than in ovulation phase. Pulse wave velocity and pulse pressure amplification was negatively correlated to progesterone in follicular phase. The arterial stiffness increased at ovulation and decreased in follicular and luteal phases of menstrual cycle. Conclusions: No significant correlation between arterial stiffness parameters and ovarian hormones was found.